The Malaysian code of corporate governance: an effort to improve the quality of financial reporting / Wan Adibah Wan Ismail and Khairul Anuar Kamarudin - Wan Ismail, Wan Adibah; Kamarudin, Khairul Anuar (Faculty of Accountancy, UiTM Kedah, 2018)
Several initiatives were taken by the policy makers and regulators to improve the quality of financial reporting by Malaysian companies. One of the initiatives was to strengthen the corporate governance of Malaysian public listed companies by introducing a code of corporate governance. The Malaysian Code on Corporate Governance was drafted in 1999 and introduced in March 2000. The code was then revised in 2007 to include additional recommendations relating to the board of directors and audit committees. The code was basically issued to serve as a guideline to enhance corporate governance practices among public listed companies in Malaysia.